Personality, Coping and Developmental Conditions in Female Adolescents and Young Adults with Type 1 Diabetes: Influence on Metabolic Control and Quality of Life - Wagner, Gudrun; Zeiler, Michael; Karwautz, Andreas; Schneider, Andrea; Rami-Merhar, Birgit; Berger, Gabriele (Frontiers in Psychiatry, 2022)
Objective: To assess personality factors, coping, developmental conditions and quality of life in female adolescents and young adults with type 1 diabetes (T1D) and high versus low HbA1c. Methods: Patients were approached at the Department for Pediatrics, Medical University of Vienna; n=129 female adolescents (10 to 23 years, mean age 15.21 2.91) with type 1 diabetes were included. HIGH-A1c was defined as HbA1c >7.5%, LOW-A1c as HbA1c ≤ 7.5% and compared to a sample of 56 age-matched female healthy controls. Self-rating questionnaires were used to assess psychosocial factors: Children’s Depression Inventory (CDI); Junior Temperament and Character Inventory (J-TCI); Eating Disorders Inventory-2 (EDI-2); KIDCOPE; Subjective Family Image Test (SFIT) and Inventory of Life Quality in Children and Adolescents (ILC). Results: T1D patients with HIGH-A1c were younger at the age of diabetes onset, had a longer diabetes duration, a higher maximum BMI, higher depression score, and higher frequency of diabetic ketoacidosis in the last year. They showed significantly higher levels of fatigue, lower levels of taking responsibility, lower ability to set goals and lower self-acceptance, as well as higher levels of ineffectiveness, lower levels of emotional attachment within the family, in particular with the fathers, and used negative coping strategies more often compared to patients with LOW-A1c. Furthermore, they reported significantly higher burden of illness and lower quality of life. Conclusions: Disadvantageous personality and coping styles as well as developmental conditions should be addressed in the treatment of female adolescents with T1D with management problems.